The effect of summer on value-added assessments of teacher and school performance - Gregory J Palardy; Luyao Peng (Arizona State University, 2015)
This study examines the effects of including the summer period on value-added assessments (VAA) of teacher and school performance at the early grades. The results indicate that 40-62% of the variance in VAA estimates originates from the summer period, depending on the outcome. Furthermore, when summer is omitted from the VAA model, 51-61% of the teachers and 58-61% of the schools change performance quintiles, with many changing 2-3 quintiles. Extensive statistical controls for student background and classroom and school context reduce these differences, but 36-47% of the teachers and 42-49% of the schools are still in different quintiles. Besides misclassifying teachers and schools, including summer creates biases in VAA estimates against schools with concentrated poverty. These results suggest that removing summer effects from VAA estimates will likely require biannual achievement assessments (i.e., fall and spring).